Visualization of membrane-associated R-plasmid DNA in fraction of Escherichia coli minicell lyzate - Hochmannová, J; Nesvera, J; Stokrová, J (Folia microbiologica, 1980)
Minicells of Escherichia coli P678-54 containing plasmid RIdrd19 were submitted to careful controlled lysis. By sedimentation of the resulting lyzate in a sucrose gradient, the material absorbing at 260 nm was separated into three distinct bands. Among the most rapidly sedimenting particles, double-stranded topological circles of DNA attached to patches of membrane were visualized by electron microscopy, while single-stranded molecules (probably RNA) with associated proteins were detected in the medium band. Covalently closed and open circles of the RIdrd19 DNA were found at the top of the gradient. Their contour lengths correspond to the size of the DNA sedimenting together with the membrane in the first peak. This finding implies a direct intracellular interaction between RIdrd19 DNA and membrane in E. coli minicelle.
Keywords: R Factors; bakteriolýza; DNA, Circular; Centrifugation, Density Gradient; centrifugace - gradient hustoty; DNA, Bacterial; kruhová DNA; Bacteriolysis; buněčná membrána; Escherichia coli; Microscopy, Electron; R-plasmidy; DNA bakterií; Cell Membrane; elektronová mikroskopie